Ear Training for Twentieth-Century Music - Friedemann, L. Michael (New Haven, CT Yale University Press, 1990)
Michael Friedmann's Ear Training for Twentieth-Century Music is a skills text; using non-tonal materials, students are asked to improvise at the keyboard, sing at sight, take dictation, memorize melodies by rote, and identify selected set classes by eye and ear.
Keywords: 20th Century (1901-2000)